Growth and Immune Response of Pangasius hypophthalmus Fed Diets Containing Seaweed Extracts as Immunostimulant - Baleta,Francis Nuestro (2019)
Abstract Growth and immune response of Pangasius hypophthalmus were evaluated after feeding the fish with diets containing hot-water extracts (HWE) of Sargassum oligocystum as immunostimulant at 100, 300, and 500 mg kg-1 diet. Basal diet for P. hypophthalmus served as the control. The experimental diets were administered for 12 weeks. At the end of the feeding experiment, growth and haematological profile of fish were evaluated. Result showed that final weight, weight gain, daily growth rate and feed conversion ratio were significantly increased in the fish that received 300 and 500 mg kg-1 HWE of S. oligocystum. Evaluation of the haematological profile showed that white blood cells red blood cells, hemoglobin, hematocrit and platelet of P. hypophthalmus that received the HWE of S. oligocystum were significantly higher than the control group. Overall, our results indicate that the use of S. oligocystum HWE improves growth and haematological profile in P. hypophthalmus.